Long-term daily feeding of cannabidiol is well-tolerated by healthy dogs - Bradley, Sophie; Young, Scott; Bakke, Anne Marie; Holcombe, Lucy; Waller, Daniel; Hunt, Alysia; Pinfold, Kathleen; Watson, Phillip; Logan, Darren W. (Frontiers in Veterinary Science, 2022)
Cannabidiol (CBD) containing dog food and treats are widely commercially available, mirroring the growing popularity of CBD as a supplement for humans. Despite this, experimental evidence of the safety and efficacy of long-term oral exposure in dogs is lacking. The purpose of this study was to address the gap in knowledge around the longer-term suitability and tolerance of a broad-spectrum CBD (THC-free) distillate in clinically healthy dogs. The study was a randomised, placebo-controlled, and blinded study where one group of twenty dogs received daily CBD capsules at a dose of 4mg/kg of body weight (BW) for a period of six months. The control group of twenty dogs received placebo capsules. A comprehensive suite of physiological health measures was performed throughout the study at baseline, and after 2, 4, 10, 18, 26 weeks of exposure, followed by four weeks of washout. CBD concentrations were measured at the same cadence in plasma, faeces and urine. Health measures included biochemistry, haematology, urinalysis, in addition to fortnightly veterinary examinations, twice daily wellbeing observations, and a daily quality-of-life survey. Biochemistry and haematology showed no clinically significant alterations apart from a transient elevation in alkaline phosphatase (ALP) in just over half of the dogs receiving CBD. This elevation was observed in the absence of concurrent elevations of other liver parameters, and without any adverse effects on health and wellbeing. Furthermore, bone alkaline phosphatase (BALP) was simultaneously elevated with a significant, strong (r > 0.9) positive correlation between the two measures, suggesting that the elevation of total ALP was at least partly due to the bone-derived isoform. This study provides evidence that a once-daily oral dose of 4mg CBD/kg BW is well tolerated in clinically healthy dogs for a duration of six-months.